669 Preventing concussion in youth ice hockey: is research evidence necessary to inform policy change. (1st September 2016) - Emery, CA; Krolikowski, M; Black, A; Meeuwisse, WH; Nettel-Aguirre, A; Goulet, C; Hagel, BH
Abstract : Background: Participation and concussion rates in youth ice hockey are high. The objective is to evaluate the effectiveness of evidence-informed policy change delaying the age of body checking in youth ice hockey compared to a rule enforcement policy change "zero tolerance for head contact" that was not evidence-informed, in reducing the risk of concussion in youth ice hockey players. Methods: This cohort study included competitive ice hockey players (ages 11–14) in leagues where body checking commenced at age 11 (n = 1408) and leagues where body checking was delayed until age 13 (n = 1366). In addition, player cohorts (ages 11–14) before (n = 1269) and after (n = 830) the "zero tolerance for head contact" rule enforcement were compared. Validated injury surveillance methodology was used. The primary outcome was game-related concussion. Results: Based on multiple Poisson regression analyses (adjusted for cluster and other covariates and using exposure hours as an offset), the incidence rate ratio (IRR) associated with policy disallowing body checking for 11 and 12 year old players was 0.2 (95% CI: 0.08–0.51) for concussion. For 13 and 14 year old players, being in a league that allowed body checking since age 11 was not protective of concussion [IRR = 0.87 (95% CI: 0.51, 1.50)]. The IRR associated with the head contact rule enforcement change in 11–12 year old players was 1.85 (95% CI: 1.20–2.86) and in 13–14 year old players was 2.48 (95% CI: 1.17–5.24) for concussion. Concussion risk increased following the head contact rule enforcement change. Conclusions: Evidence-informed policy change delaying body checking to age 13 in youth ice hockey prevents concussions in 11–14 year old ice hockey players. Head contact rule enforcement policy change (not evidence-informed) did not reduce the risk of concussion. Referral bias related to a greater awareness of concussions in youth ice hockey may have accounted for the higher concussion rate following the 2011 policy change.